Right from the start : behavioral intervention for young children with autism - Harris, Sandra L. 4 0 16; Weiss, Mary Jane; 5 (Bethesda, MD : Woodbine House, 2007)
Explains the benefits of using the intensive behavioral intervention method of teaching when working with young students diagnosed with autism and autism-related disorders.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Behavior modification. -- Autistic children;Autistic children.;Behavior modification; 20; 2